Accessibility in Collection Development in Academic Libraries in Manitoba, Nova Scotia, and Ontario - Hayes, Agnieszka; Hayes, Joseph (Partnership, 2025)
Accessibility in collection development policies (CDPs) and practice in Canada is understudied. Two studies focusing on academic libraries in provinces with accessibility legislation were done to investigate both policy and practice. The first study employed a content analysis of publicly available CDPs of academic libraries in Manitoba, Nova Scotia, and Ontario to determine if accessibility was explicitly mentioned in them. The study aimed to explore possible legislative influence in the wording of CDPs. Since CDPs show only part of the picture as to how selectors make their acquisition decisions, in the second study, a multiple-choice and short answer survey was administered to selectors at academic libraries in these three provinces, in order to discover the factors that influence selectors in deciding if and how they use accessibility as a selection criterion. This article presents the research undertaken and sheds new light on how accessibility functions in collection development in the Canadian academic library context.